Impact of decision horizon on post-prognostics maintenance and missions scheduling: a railways case study. Issue 4 (4th July 2022) - Bougacha, Omar; Varnier, Christophe; Zerhouni, Noureddine
ABSTRACT: In this paper, we propose a study of the decision horizon duration for rolling stock mission assignment and maintenance planning in a prognostics and health management (PHM) context. The aim is to determine the best decision horizon duration that allows the construction of a suitable schedule that assigns railway vehicles to missions and integrates required maintenance operations according to the current and future health of the vehicles. A genetic algorithm is used to minimize the overall cost of the joint schedule as a function of the decision horizon. The results are compared to three proposed heuristics to study the influence of the resolution method on the decision horizon duration. The best decision horizon duration is given for each used method for an illustration case.